Synthesis and Anti-microbial Activities Investigation of New Mixed Ligand Complexes - A. Mousa, Elaf; I. Al-Abdaly, Basim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Transition ion complexes have various commercial and technical uses, including antibacterial, antifungal, and anticancer medications and catalysts; their characteristics are critical regarding their kinetic impact. This study aims to synthesize new complexes, copper and nickel complexes, characterize them using spectral techniques, determine their chloride content, evaluate their anti-oxidant effect, and examine the antibacterial activity of the ligands and their complexes against gram-positive bacteria (Staphylococcus), gram-negative bacteria (Escherichia coli), and Candida albicans. All chemicals were used strictly as provided, with no additional purification; CuCl2.2H2O and Ni(CH3CO2)2 salts were used to react with melatonin (L1), and one of the amino acids (L-cysteine) (L2) in a mole ratio of 1:1:1 (M: L1:L2) to produce mixed ligand metal complexes. The results showed that the two metal complexes were more active in (10–3 M) and had higher activity than the two ligands (melatonin and cysteine). According to the findings, the complexes have suggested structures: octahedral geometry for the Cu(II) complex and tetrahedral geometry for the Ni(II) complex. The scientific results demonstrated that the synthesized complexes have high antibacterial action against [Escherchiacoli (G-) (E. coli), Staphylococcus aureus (G+)], and antifungal action against [Candida (C. albicaus)].